Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori